On the localization of invariant Tori in a family of generalized standard mappings and its applications to scaling in a chaotic sea - da Costa, Diogo Ricardo [UNESP]; Caldas, Iberê L.; Ladeira, Denis G.; Leonel, Edson D. (L and H Scientific Publishing, 2018)
The localization of the last invariant spanning curve - also known as the last invariant tori - in a family of generalized standard mappings is discussed. The position of the curve dictates the size of the chaotic sea hence influencing the scaling properties observed for such region. The mapping is area preserving and is constructed such its dynamical variables are the action, J, and the angle θ . The action is controlled by a parameter ε, controlling the intensity of a generic nonlinear function, which defines a transition from integrable for ε = 0 to non integrable for ε ≠ 0. The angle is dependent on a parameter γ. If γ > 0, the angle has the property that it diverges in the limit of vanishingly action and is added, by a finite function dependent on a free parameter γ, when the action is larger than zero. The case γ = -1 reproduces the expression of the angle for the traditional standard mapping. The phase space is mixed and shows, for certain ranges of control parameters, a set of periodic islands, chaotic seas and invariant spanning curves. Statistical properties for an ensemble of noninteracting particles starting in the chaotic sea with very low action is considered and we show: (i) the saturation of chaotic orbits grows with εα ; (ii) the regime of growth scales with nβ and (iii) the regime that marks the changeover from the diffusive dynamics to the stationary state scales with ε z. The exponents α and z depend on γ and are independent of the nonlinear function f while β is universal. To illustrate the theory here proposed, we obtain an estimation for the critical parameter Kc for a generalized standard mapping considering three different periodic functions. We also find α β and z for different nonlinear functions.
Keywords: Chaos; Chaotic sea; Generalized standard mappings; Invariant tori